What ethical challenges arise in global health programmes? A qualitative case study of global health programme leaders’ experiences - James V Lavery; Michelle Grek; Ashley Graham; David Addiss (BMJ Open)
Objectives The study aimed to describe the ethical challenges global health programme (GHP) leaders encounter in their day-to-day work and to understand how they address these ethical challenges, as an important first step toward improving the relevance and precision of ethical guidance for GHPs.Design We employed a qualitative case study approach using grounded theory data collection and analysis methods.Setting GHPs based at a major GHP hub in Decatur, Georgia, USA, providing a wide range of health services to more than 150 countries globallyParticipants Leaders of all 15 GHPs in the programme hub were invited to participate and 9 were available and consented to participate. Two senior leaders of the programme hub also participated in the study.Results We identified 10 categories of ethical challenges encountered by GHP leaders: (1) ethical misalignment between funders and implementing partners; (2) budgets functioning as constraints on ethical decision-making; (3) the limited impact of programmes on improving host country capacity; (4) concerns about missed opportunities to benefit host country communities; (5) shortcomings in current ethics guidance (6) issues in data governance, stewardship and management; (7) navigating complex sociocultural contexts; (8) photography in the context of GHPs; (9) trustworthiness and reputational risks and (10) accountability for unintended consequences. The challenges often result in divided or conflicting loyalties for GHP leaders and uncertainty about what to do. We have characterised this form of uncertainty as ‘moral ambiguity,’ which we define as the inability to discern the best ethical way forward when there is tension or conflict among multiple stakeholder interests.Conclusions Our findings suggest that moral ambiguity is a common experience for GHP leaders and that current approaches to global health ethics fail to guide and support GHP leaders to recognise and address moral ambiguity and limit the distress it can cause. The experiences of GHP leaders offer important diagnostic insights for improving the way GHPs are imagined, financed, delivered and evaluated.